Law, poverty, and legal aid : access to criminal justice - Muralidhar, S. (New Delhi : LexisNexis Butterworth, 2004)
In the Indian context.
Includes bibliographical references (p. [xlvii]-lxv) and index.
Keywords: Legal aid -- India; Defense (Criminal procedure) -- India; Legal assistance to the poor -- India